Etnopedologia no conhecimento ambiental - Ernesto Sobrinho, Francisco (Universidade Federal Rural do Semi-Árido, 2015)
The growing scientific concern for sustainable development and appropriate use of natural resources has awakened to the need for research on participatory approach, bringing researchers and farmers. The main hypothesis of this work is the study of the farmer knowledge used as tools observations experienced in activities over the years, the respect of the problems and solutions for their systems and that this knowledge is in line with the scientific knowledge. Consistent with the idea of integration of knowledge and considering the few studies with ethnopedological approach developed in the state of Rio Grande do Norte. This study is a way, the one record that despite never forget the land of his birth, moved, traveled by other plagues; studied, learned, reflected, matured and now back to the beloved land, seeking to portray it at the same time, meet a heart pulse and rethink what you have learned. Given the above, it was aimed to perform ethnopedological evaluation of Sant Miguel Ranch, and thus prepare the pedological survey, characterize the fauna and flora and the use made of them, know the sources and use of water providing understanding of reality site. In no approach analyzes and scientific names, but also the record of the wisdom of the ancients; own observations collected over many years and notes while listening to the considerations of those who came before. The study was conducted in the city of Almino Afonso (where the ranch ridge de Saint Miguel, along with 29 other sites, is in the mountainous area of the middle-west of the state of Rio Grande do Norte, on the border with Paraíba, on the splitter water: Piranhas (south) and Apodi (north). The main results identified three general elements of greater importance in the characterization Ranch of Ridge environment of San Miguel: the mountainous terrain, the stony ground and the trees and shrub thick. The strong rocky relief wavy and thick vegetation, unfavorable to the penetration of extensive cattle ranching, slow to occupation of the local area in colonial times. It was concluded that the soil in this study, although stony, provided adequate natural fertility to sustain agriculture with empirical techniques, a factor that induced the backcountry search saws because they have higher rainfall for its water supply, and production of easy pickings in the backwoods farmer
Ethnopedology in environmental knowledge
Tese
Keywords: Pedology; Sítio Serra de São Miguel Almino Afonso/RN; Hinterland depression; Peasant - experiences; Emic; Pedologia; Sítio Serra de São Miguel Almino Afonso/RN; Depressão sertaneja; Camponês - vivências; Emicista; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO